Approaches to the Archaeology of Food - Samuel, Delwen (Petits Propos Culinaires, 2024)
The author, with Mark Nesbitt, was organiser of a pioneering series of seminars on Archaeology and Food held at the Institute of Archaeology, University College London, early in 1996. We invited her to convert her opening address into an essay for PPC, to give our readers an idea of how archaeologists, on the eve of the next millennium, view the challenges and opportunities which confront them in dealing with all the manifold aspects of food.